Cancer Therapy with Polymeric Nanocarriers and the Transition to Targeted Cancer Therapy: Advances and Future Directions - Theodosis-Nobelos, Panagiotis; Kitiri, Elina N.; Christou, Melina; Pantelidou, Maria; Rikkou-Kalourkoti, Maria (Pharmaceutical Nanotechnology, 2025)
The development of targeted cancer therapies has become crucial in addressing the limitations of conventional chemotherapy, particularly its lack of specificity and severe side effects. Polymeric nanocarriers have emerged as a transformative solution, providing enhanced drug solubility, selective targeting, and controlled release of therapeutics. This review discusses recent advances in polymeric nanocarriers, emphasizing their capacity to incorporate multiple drugs and optimize delivery through both active and passive targeting strategies, and especially the transition to targeted cancer therapy through the various applied methods in the field. Mechanisms such as the enhanced permeability and retention (EPR) effect for passive targeting, and the use of ligands, peptides, and proteins for active targeting, are explored in depth. Furthermore, the potential of these nanocarriers to improve therapeutic outcomes through targeting specific cellular and subcellular sites, including the nucleus, mitochondria, and endoplasmic reticulum, is examined. These innovations pave the way for the development of safer and more effective cancer treatments with the potential to enhance clinical outcomes.
Keywords: ligand -receptor interactions